Pedagogies of the South and political subjectivation: People´s High Schools in Argentina as part of "Latin American pedagogical movements" - Shirly Said (Arizona State University, 2018)
In this article we recover the perspective of the sociology of emergencies and link the proposal of decolonial thinking with critical Latin American pedagogies. With this conceptual framework, and going through different conceptions of political subjectivation, we propose to approach the experience of People´s High Schools for Young People and Adults in Argentina (BPJA, for its acronym in Spanish) as part of the Latin American pedagogical movements oriented to the critical reconstruction of pedagogical knowledge. The BPJA are high schools for young people and adults that work in a self-managed way within the framework of territorial organizations and recovered factories, and carry out a political-pedagogical project linked to popular education with an emancipatory horizon. They demand that the State guarantees the right to education for all social sectors, while defending the political and pedagogical autonomy of their curriculum. Within the new social, political and -therefore- pedagogical ways of construction of various Latin American social movements, we propose that the BPJA are a significant expression of the gestation of emerging alternatives, which with great creative and self-reflective potential have managed to stress certain traditional forms of education, orienting themselves to the formation of political and critical subjects, and transforming themselves into collective pedagogical subjects.